(untitled) (Vietnam Journal of Community Medicine, 2026)
Objective: To describe endoscopic characteristics based on the WASP classification and evaluate the outcomes of cold snare polypectomy for non-pedunculated polyps smaller than 10 mm. Methods: A Pilot study was conducted on 30 patients who underwent colonoscopy at Phuong Chau International Hospital in Can Tho and Phuong Chau International Hospital in Soc Trang from May 2025 to August 2025. All polyps smaller than 10 mm were removed using cold snare polypectomy. Clinical, endoscopic, and histopathological characteristics and complications were analysed. Results: The mean age was 45.6 ± 11.6 years; females accounted for 56.7%. A total of 65 polyps were identified, with the majority located in the left colon (43.1%) and the right colon (41.5%). Serrated polyps accounted for 7.7%. Positive WASP classification was observed in NICE 1 (15.4%) and NICE 2 (12.8%). The complete resection rate was 100%. The rate of early bleeding complications was low (3.3%), with no delayed complications recorded. Conclusion: Endoscopy with WASP classification is valuable in lesion identification. Cold snare polypectomy is a safe and effective method for removing small non-pedunculated colorectal polyps.